Teaching and Learning of Visual Arts in Senior High Schools in Rural and Urban Settings in Ghana (International Journal of Technology and Management Research, 2020)
This study used qualitative and quantitative research methods in tandem to compare teaching and learning processes to illuminate differences in students' academic performance gap in the Visual Arts in urban, peri-urban and rural Senior High Schools in the Ashanti Region. With the use of purposive and simple random sampling techniques, a sample of six schools – two in each setting, comprising 120 students and 18 teachers were selected for in-depth study. The study found that urban schools perform better than rural schools because they have prestigious names and character, more qualified teachers, and they attract and admit high performance BECE applicants into the Visual Arts department. The study revealed that the geographical settings of the school and educational opportunities directly influence the academic performance and achievement of students. Environmental factors, lack of studio facilities, and differences in teaching methodologies in the different geographical settings seem to influence students' learning and performance.Keywords: Teachingandlearning;Visualarts;Ruralandurbaneducation;Academicperformance.